Planar perovskite solar cells with 15.75% power conversion efficiency by cathode and anode interfacial modification1. Issue 25 (7th July 2015) - Qian, Min; Li, Meng; Shi, Xiao-Bo; Ma, Heng; Wang, Zhao-Kui; Liao, Liang-Sheng
<x xml:space="preserve">Abstract</x> Ag NPs and Bphen modified anode and cathode interfaces result in a PCE of 15.75% in perovskite solar cells.